Occurrence of Urolithiasis and Its Surgical Management in Goats (Annals of Bangladesh Agriculture, 2022)
The objective of the study was to determine the occurrence and find a suitable surgical method of urolithiasis in goat. To achieve this objective, a retrospective study was conducted to observe the occurrence of urolithiasis in goats at Veterinary Teaching Hospital of Bangladesh Agricultural University in Bangladesh from 2011 to 2020. During this period, 265 cases of urinary obstruction were recorded out of 3237 surgical cases, where 169 cases were in goats. The highest cases of urolithiasis in goat were recorded in the summer season (76 cases 45%), followed by in the winter season (59 cases, 35%) and in the rainy season (34 cases, 20%). Among the affected goats, 42 (25%) patients were between 0 to 3 months old, (88, 52%) patients were between 3 to 8 months old and (39, 23%) patients were over 8 months old. Gender variation was seen where males were mostly affected. Goats castrated at an early age were more affected. From January 2011 to June 2020, 36 goats were treated by the procedure of tube cystostomy. Among them, 28 (78%) goats recovered successfully but 8 (22%) goats did not recover due to farmer’s improper management. This study should be helpul for the veterinarian to aware about the occurrence of urolithiasis, and proper surgical management through the tube cystostomy to save economic losses of the goat farmers.Ann. Bangladesh Agric. (2021) 25 (2) : 1-12